ADAPTATION OF TECHNOLOGY IN LEARNING AS AN EFFORT TO FACE GLOBAL CHALLENGES - Jumardi Budiman (Jurnal Scientia, 2023)
The main objective of this research is to gain a deeper understanding of the extent to which the use of technology can be effective in the context of learning, recognize key challenges that arise, and explore opportunities that can be optimally utilized. With deeper insight into the role of technology in education, it is hoped that this research can make a positive contribution to the development of global educational thinking and practice. Through the literature review method, this study identifies literature sources with keywords related to technology adaptation in learning and global challenges. This research presents literature findings to understand the effectiveness of using technology in learning, identify key challenges, and explore emerging opportunities. The results show that technology adaptation in learning is a critical focus in improving the quality of education in the digital era. Aspects such as student learning outcomes, teaching quality, and student engagement levels are key assessments of technology's effectiveness in education. Numerous studies have shown that the integration of technology can improve the quality of learning and student motivation, provide wider access to educational resources, and enable personalized learning. However, challenges such as access gaps, low digital literacy, and policy barriers are obstacles in the implementation of learning technology. Emerging opportunities include increased teacher creativity, differentiated learning, global collaboration, increased student engagement, and deep learning analytics. This research makes a positive contribution to global educational thinking and practice by providing an in-depth understanding of the role of technology in addressing global challenges. In conclusion, good coordination between innovative learning design, comprehensive teacher training, and strong infrastructure support is required to create an optimal learning environment in the digital age.